Manajemen Kebijakan Kartu Indonesia Pintar Dalam Mewujudkan Pemerataan Pendidikan Di SMP Negeri Kota Bandung - Ma'rifah Aini, Nur; Tutty R. Rosa, Ade; Ratnawulan, Teti (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
This study focuses on the analysis of the Smart Indonesia Card (KIP) policy in junior high schools in Bandung City to understand its effectiveness in promoting educational equality. The purpose of the study was to identify supporting and inhibiting factors for this policy, and to offer solutions for improvement. Using a qualitative method with a descriptive case study approach, data were collected through observation, interviews, and documentation. The results of the study indicate that the KIP distribution mechanism has been running, but socialization and targeting accuracy are still less than optimal. Some students in need do not receive benefits, while students from well-off families do. Supporting factors include ease of access to information, while inhibiting factors include administrative constraints and data synchronization. Recommendations include giving schools more authority in making decisions related to KIP, intensifying supervision, and awareness from the community who are already well-off to stop assistance.